FORMATION OF MEDICAL TERMS AND THEIR LINGUISTIC, COMMUNICATIVE ASPECTS (Journal of Universal Science Research, 2024)
This article provides information on the formation of medical terms. Linguistic and communicative aspects of anatomical terms, construction structure of terms and importance in medicine are discussed based on analysis with examples.